Sequence And Functional Analyses Of Salinity Tolerance Genes Isolated From The Mangrove Plant, Acanthus Ebracteatus (Sea Holly) - Nguyen, Phuoc Dang (2005)
Salinity is a major abiotic stress that greatly affects plant growth and crop production. Most trees and crop plants are sensitive to salty conditions. Sodium ions are toxic to plants because of their adverse effects on potassium nutrition, cytosolic enzymes activities, photosynthesis and metabolism. Mangrove plants are good models to study plant tolerance to salinity as they possess salinity tolerance genes that allow them to survive under with high salinity conditions. The objectives of this study are to identify, isolate and characterize salinity tolerance genes from a mangrove plant, Acanthus ebracteatus using expressed sequence tag (EST) and bacterial functional assay approaches. The leaves of A. ebracteatus were collected from the mangrove area at Morib, Selangor. Total RNA was isolated from the leaves of A. ebracteatus, and a cDNA library was constructed from cDNA fractionated between 500 to 5,000 bp. A total of eight hundred sixty four randomly selected clones were . . . I l l isolated from the primary cDNA library from which 521 clones were sequenced. Among these ESTs, 138 of them were assembled into 43 contigs whereas 383 were singletons. A total of 349 of these ESTs showed significant homology to functional proteins and 18 % of them are particularly interesting as they correspond to genes involved in the stress response. Some of these clones, including mannitol dehydrogenase, plastidic aldolase, secretory peroxidase, ascorbate peroxidase, and vacuolar H'-ATPase, may be related to salinity tolerance mechanisms such as osmotic homeostasis, ionic homeostasis and detoxification. In this study, a bacterial functional assay was also performed to identify cDNAs that confer salinity tolerance. A total of 120 salinity tolerant candidate genes from A. ebracteatus were isolated from 2 X YT medium supplemented with 400 mM NaCl and sequenced. Among these clones, 27 of them may be related to salinity tolerance such as manganese superoxide dismutase (Mn- SOD), putative salt tolerance protein, glutathione S-transferase, etc. The results showed that plants and bacteria may share some similar mechanisms for salinity tolerance. A total of six cDNA clones from A. ebracteatus were fully sequenced and three of them were characterized by Southern hybridization and Northern hybridization. Clone A290 encoded a putative plastidic aldolase that may be involved in osmoprotection by converting triose phosphate into hexose. This gene was found to be expressed predominantly in the leaves of A. ebracteatus. There may be more than one family member of plastidic aldolase in A. ebracteatus. Meanwhile, clone A303 was found to be a putative H'-ATPase, an enzyme known to play an important role in ion homeostasis, a salinity tolerance mechanism. This gene most probably exists as a single copy gene in A. ebracteatus. The expression of H'-ATPase was detected in all tissues of A. ebracteatus. Clone A325 encoded a putative monodehydroascorbate reductase which is involved in the detoxification mechanism. This gene was also expressed in all tissues and is most probably a single copy gene in the genome of A. ebracteatus. Sequence analysis of the putative salinity tolerant cDNAs isolated by bacterial functional assay and ESTs suggested that the salinity tolerance mechanisms in A. ebracteatus may involve ion homeostasis, osmotic homeostasis, detoxification and other supporting mechanisms.